Drug Therapy of Attention Deficit Hyperactivity Disorder: Current Trends - De Sousa, Avinash (Medknow Publications & Media Pvt Ltd, 2012)
Attention deficit hyperactivity disorder is a developmental disorder with an age onset prior to 7 years. Children with ADHD have significantly lower ability to focus and sustain attention and also score higher on impulsivity and hyperactivity. Stimulants, such as methylphenidate, have remained the mainstay of ADHD treatment for decades with evidence supporting their use. However, recent years have seen emergence of newer drugs and drug delivery systems, like osmotic release oral systems and transdermal patches, to mention a few. The use of nonstimulant drugs like atomoxetine and various other drugs, such as α-agonists, and a few antidepressants, being used in an off-label manner, have added to the pharmacotherapy of ADHD. This review discusses current trends in drug therapy of ADHD and highlights the promise pharmacogenomics may hold in the future.